Pengaruh Kualitas Sistem Informasi Cyber CampusTerhadap Kepuasan Dan Loyalitas Mahasiswa STIKOM Surabaya - Puspita Kartikasari (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2017)
Development of Information Technology that occur provide various tools for universities to improve the quality of service to its academic community. One of the things that has been done to sustain the existing information systems in the campus environment is to create a website. Therefore, this research is devoted to the use of web-based academic information systems at the Institute of Business and Informatics Stikom Surabaya known as Cyber Campus Information System (SICYCA). Through SICYCA, students can easily obtain data on a wide range of services, such as Academic, Finance, PPTA, Library, E-Resource, Email, Community. SICYCA has some constraints in the usage, but SICYCA is still used by students for the benefit of the learning process. Thus, a study is required about measuring the influence of the quality of SICYCA on satisfaction and loyalty of students Stikom Surabaya to know what influences student satisfaction towards SICYCA. This study uses WebQual 4.0 modified by adding the dimension of the quality of the user interface. Data were collected using questionnaires, then carried the description on the data obtained and the data processing is done using Structural Equation Modelling analysis. The results of the analysis showed that the variables that significantly influence student satisfaction is the quality of usability and the user interface design quality, while student satisfaction has very significant effect on student loyalty.